Assessment of activity of ocular sarcoidosis by gallium scanning. Issue 5 (May 1987) - Karma, A; Poukkula, A A; Ruokonen, A O
Abstract : Gallium (67Ga) citrate uptake over the orbits, parotid glands, and lungs was examined in six newly detected patients with sarcoidosis and 17 with chronic sarcoidosis. Six of 23 (26%) had uveitis, 18/23 (78%) decreased lacrimal secretion, and 13/16 (81%) epithelioid cell granulomas in conjunctival biopsies. Ten patients with other diseases served as controls. Only five patients had ocular complaints and two had enlarged parotid glands. 67Ga uptake over the orbits and parotids was measured by a quantitative computer based method. Gallium uptake was significantly higher over the orbits (p less than 0.001) and parotids (p less than 0.01) in the newly detected patients and in the parotids (p less than 0.01) in the chronic group than the corresponding uptake in the controls. We suggest that in sarcoidosis an increased 67Ga uptake in the orbital and parotid areas may be a phenomenon comparable to an increased 67Ga uptake in the lungs in active alveolitis. Gallium scan is a good method for revealing even symptomless ophthalmic sarcoid changes. However, in chronic sarcoidosis an equal or only slightly increased gallium uptake over the orbits compared with background activity does not exclude ocular sarcoid disease.